Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1463-6395.2002.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glial cells in the central nervous system of the pulmonate snail Megalobulimus oblongus identified by means of a glial fibrillary acidic protein marker

Abstract: The distribution of the glial cells in the pulmonate gastropod Megalobulimus oblongus was studied by means of an immunohistochemical procedure. These cells expressed glial fibrillary acidic protein in their cell bodies as well as in their processes. In all ganglia of the central nervous system, four types of glial cells were identified. The glial lacunar network and the perineuronal glial cells were found in the cortical region of the ganglia, and the perisynaptic and the fibrous glial cells in the neuropilar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Accordingly, GFAP-like immunoreactivity has been shown in enteric glia (Jessen and Mirsky, 1980), Schwann cells of unmyelinated peripheral nerve fibers (Yen and Fields, 1981;Dahl et al, 1982), lens epithelium (Hatfield et al, 1984), and Kupffer cells in the liver (Gard et al, 1985), among others. Filaments of morphological structure similar to the intermediate glial filament have been reported in the glial cells of many mammals, birds, reptiles, fishes (Dahl et al, 1985), and in some invertebrates such as annelids and mollusks (see Radojcic and Pentreath, 1979;Cardone and Roots, 1990;Riehl and Schlue, 1998;Dos Santos et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
“…Accordingly, GFAP-like immunoreactivity has been shown in enteric glia (Jessen and Mirsky, 1980), Schwann cells of unmyelinated peripheral nerve fibers (Yen and Fields, 1981;Dahl et al, 1982), lens epithelium (Hatfield et al, 1984), and Kupffer cells in the liver (Gard et al, 1985), among others. Filaments of morphological structure similar to the intermediate glial filament have been reported in the glial cells of many mammals, birds, reptiles, fishes (Dahl et al, 1985), and in some invertebrates such as annelids and mollusks (see Radojcic and Pentreath, 1979;Cardone and Roots, 1990;Riehl and Schlue, 1998;Dos Santos et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
“…The sections were again washed and then incubated in either streptavidin complex (Amersham) diluted 1 : 100 or PAP (Sigma) diluted 1 : 500 in PBS for 1.5 h at room temperature. For the localization of peroxidase activity, the sections were preincubated for 10 min in 0.06% 3,3′‐diaminobenzidine tetrahydrochloride (Sigma) dissolved in PBS, and then incubated for 10 min in the same solution containing 0.001% H 2 O 2 at room temperature (Santos et al . 2002a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, M. abbreviatus displayed vimentin and GFAP immunoreaction in the CNS, which was detected in small glial bodies and their processes. In relation to their localization through any nervous ganglion, four types of glial cells were detected in this snail, using the GFAP marker: the glial lacunar network and the perineuronal glial cells were found in the cortical region, while the perisynaptic and the fibrous glial cells were found in the neuropilar or medullar region (Santos et al . 2002a,b).…”
Section: Introductionmentioning
confidence: 99%
“…NFs have not been observed in crustaceans using conventional electron microscopy, and IFs in general have not been observed in crustaceans and other arthropods by immunocytochemistry. However, numerous studies in lower vertebrates and invertebrates have revealed the presence of NF proteins similar to mammalian NF subunits (Philips et al 1983;Viancour et al 1987;Leapman et al 1997;Karabinos et al 2001) and IF like glial fibrillary acidic protein (GFAP) (Cardone and Roots 1990;Kumar et al 1996;Riehl and Schlue 1998;dos Santos et al 2002). Particularly interesting for crustacean neurobiologists was the study conducted by Weaver and Viancour (1991), representing a very thorough search for mammalian NF proteins in crayfish axons: following labeling with the commercially available anti-NF-M monoclonal antibody (NN18-clone), it revealed a polypeptide located on microtubule side-arms.…”
Section: Introductionmentioning
confidence: 99%